AKUNTABILITAS PENGELOLAAN DANA DESA PADA DESA SUBAN AYAM KECAMATAN SELUPU REJANG KABUPATEN REJANG LEBONG - Tri Juniarti; Anggie Novrie (Politeknik Raflesia Press, 2021)
Abstract - This study aims to determine how the administration, reporting and accountability of village funds in Suban Ayam Village, Selupu Rejang District, Rejang Lebong Regency, Bengkulu Province. This research method is descriptive qualitative. Sources of data are primary data and secondary data. Data collection techniques were interviews, and documentation and conclusions were drawn using qualitative analysis techniques. The results of the study show: (1) The administration is carried out by finance in the form of expenses recorded in the general treasury book, bank book and tax subsidiary ledger. (2) Delay in reporting for semester 1 due to grammatical errors. (3) Accountability The submission of accountability reports to the public through billboards/banners as well as direct submission for the convenience of the community to see the performance of the village government.